PERANCANGAN SISTEM PERSEDIAAN BARANG JADI PADA PT.ULTRA PRIMA PLAST JAKARTA - Rusanti, Karlina; Ferliyanti, Herlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of the inventory of which is to meet consumer demand with rapid, to support the activities of the companies concerned. In addition to the inventory information is important to provide information about the financial position of the fair as a going concern. Inventories of goods are also very susceptible to damage, rising prices, damage and theft. To that end, the management company must perform a system for recording the inventory appropriately in accordance with the procedures specified. Because of errors in recording inventory will affect the company's income. Records with a computerized card stock will facilitate the checking of inventory directly without having to physically check into the warehouse.